Aplikasi Data Penginderaan Jauh dan Sistem Informasi Geografis untuk Identifikasi Tingkat Keragaman Penggunaan Lahan - Dwi Nowo Martono (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
This research is examine level of variety landuse and road network by calculating entropy indeks each“Rukun Wilayah (RW)” in Cibatok subdistrict Bogor. High resolution Remote sensing “quick bird” data is usedto identify landuse and road network distribution. Base on interpetation result by remote sensing data, thereare 3 class of landuse which are rice field, mix garden and settlement. Rice field dominate 73,063% of wholeresearch area. Settlement spread each RW in Cibatok Village, The other side mix garden less spread, becauseonly in RW 03 and RW 04. The highest heterogeneous land use in RW 08 with average entropy value 0,866 andthe most homogeneous in RW 01 with entropy value 0,452. Entropy value not related with level of accessibility.Kata Kunci: remote sensing, land use, entropy